2020
DOI: 10.26434/chemrxiv.12753539.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Study on Spice-Derived Antiviral Phytochemicals Against SARS-CoV-2 TMPRSS2 Target

Abstract: We predicted the structure of TMPRSS2 (transmembrane protease serine 2), a host protein that truncates spike protein of SARS-CoV-2. Then we docked 18 anti-viral compounds found in Indian spices against the catalytic domain of TMPRSS2. We then performed rigorous molecular simulation dynamics simulation to screen the best natural phytochemical which could act as a potential inhibitor of TMPRSS2 activation. <br>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Subsequently, the catalytic domain of TMPRSS2 was docked against the eighteen selected phytochemicals. Following it, the target-inhibitor complex's stability was analyzed using molecular dynamic simulation, which indicated thymol as a better inhibitor due to their stable binding with TMPRSS2, inducing subtle modification in the spatial arrangement of the catalytic triad residues [192] .…”
Section: Thymol As a Spike Protein Inhibitormentioning
confidence: 99%
“…Subsequently, the catalytic domain of TMPRSS2 was docked against the eighteen selected phytochemicals. Following it, the target-inhibitor complex's stability was analyzed using molecular dynamic simulation, which indicated thymol as a better inhibitor due to their stable binding with TMPRSS2, inducing subtle modification in the spatial arrangement of the catalytic triad residues [192] .…”
Section: Thymol As a Spike Protein Inhibitormentioning
confidence: 99%
“…CAR also increased viral titer compared to the RSV‐PBS group, 62 but decreased levels of TLR7, MyD88, NF‐κB, and IRF mRNA in virus infected model 63 . The molecular dynamic simulation studies indicated that molecular interactions between CAR and spike protein of SARS‐CoV‐2 together with the cellular proteases TMPRSS2, showed that the CAR could inhibit the entry of the virus to the host cells 65,67 …”
Section: Resultsmentioning
confidence: 95%
“…The binding energies of these mono‐terpenoids were found to be in the range of −3.4/−3.7 kcal 66 . Molecular dynamic simulation (MDS) analysis showed CAR and thymol as better inhibitors than the camostat (a well‐known synthetic inhibitor of TMPRSS2) due to their stable binding 32 with TMPRSS2 in its oxyanion hole 67 . The results of a study suggest that the CAR could serve as potential inhibitor in regulating the main protease (M pro ) of COVID‐19 function and controlling viral replication 68 …”
Section: Resultsmentioning
confidence: 99%